21st century American English compendium : a guidebook for translators, interpreters, writers, editors, and advanced language students - Rubinstein, Marvin (Rockville, MD : Schreiber Pub., 1997)
More than just a reference book, containing Five Dictionaries in One, the Compendium tells the story of American English in an enlightening and entertaining way. It will help you gain a whole new perspective on and a much deeper understanding of the most popular language in today's world.
Guide to the Use of This Book -- Ch. 1. American Spoken Here - English Understood -- Ch. 2. Proverbs, Slogans, and Aphorisms -- Ch. 3. Popular American Expressions -- Ch. 4. Similes and Metaphors Indicating Extremes -- Ch. 5. American Slang and Colloquialisms -- Ch. 6. British vs. American English (and Vice Versa) -- Ch. 7. Foreign Words and Phrases Frequently Used in English -- Ch. 8. Acronyms, Abbreviations, and Initialisms -- Ch. 9. The Birds and the Trees -- Ch. 10. Odds and Ends.
Includes bibliographical references (p. 319-325) and index.
Keywords: English language -- United States -- Dictionaries; Americanisms -- Dictionaries